WHOLE BODY VIBRATION IMPROVES ATTENTION AND MOTOR PERFORMANCE IN MICE DEPENDING ON THE DURATION OF THE WHOLE-BODY VIBRATION SESSION - Keijser, Jan N.; van Heuvelen, Marieke J.G.; Nyakas, Csaba; Tóth, Kata; Schoemaker, Regien G.; Zeinstra, Edzard; van der Zee, Eddy A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Whole body vibration (WBV) is a form of physical stimulation via mechanical vibrations transmitted toa subject. It is assumed that WBV induces sensory stimulation in cortical brain regions through the activation of skinand muscle receptors responding to the vibration. The effects of WBV on muscle strength are well described. However,little is known about the impact of WBV on the brain. Recently, it was shown in humans that WBV improves attentionin an acute WBV protocol. Preclinical research is needed to unravel the underlying brain mechanism. As a first step, weexamined whether chronic WBV improves attention in mice.Material and Methods: A custom made vibrating platform for mice with low intensity vibrations was used. Male CD1mice (3 months of age) received five weeks WBV (30 Hz; 1.9 G), five days a week with sessions of five (n=12) or 30(n=10) minutes. Control mice (pseudo-WBV; n=12 and 10 for the five and 30 minute sessions, respectively) weretreated in a similar way, but did not receive the actual vibration. Object recognition tasks were used as an attention test(novel and spatial object recognition – the primary outcome measure). A Balance beam was used for motorperformance, serving as a secondary outcome measure.Results: WBV sessions of five (but not WBV sessions of 30 minutes) improved balance beam performance (micegained 28% in time needed to cross the beam) and novel object recognition (mice paid significantly more attention tothe novel object) as compared to pseudo WBV, but no change was found for spatial object performance (mice did notnotice the relocation). Although 30 minutes WBV sessions were not beneficial, it did not impair either attention ormotor performance.Conclusion: These results show that brief sessions of WBV improve, next to motor performance, attention for objectrecognition, but not spatial cues of the objects. The selective improvement of attention in mice opens the avenue tounravel the underlying brain mechanisms.